Consult Effectively. Issue 4 (1st August 2003) - Morrish, Paul; Balme, Max
Abstract : INTRODUCTION Consultation in outpatients is the core of neurological practice. Excuse the hyperbole, but the outpatient clinic is our operating theatre, the place where those finely honed diagnostic and therapeutic skills are demonstrated. And while neurological training has for many years concentrated on the hallowed 'where is the lesion, what is the lesion' approach to diagnosis, and – in the UK at least – the 'here is a pile of follow ups for you to wade through' approach to therapeutics and continuing care, there has been little recognition of the importance of communication skills and consultation techniques. However, things are changing rapidly. Consultation techniques are now taught and examined in medical schools and it seems inevitable that observed consultation will become part of assessment in UK neurology training, and perhaps in appraisal and revalidation for consultants as well. Good communication in consultation is not just a matter of being nice to people